Perkembangan Moral - Arnianti, Arnianti (Lembaga Yasin AlSys, 2021)
Society cannot function without rules that tell people how to communicate with one another, how to avoid hurting others, and how to get along in life in general. Children and teenagers have different understandings of rules. Likewise, teenagers have different views from their parents and vice versa. This indicates a development in the reasoning and morals of the individual. Moral development (moral development) includes the development of thoughts, feelings, and behavior according to the rules and habits regarding the things a person should do when interacting with others.